Organization of Apple (Malus domestica Borkh.) Fruit Drying and Storage Technology in the Conditions of Sirdarya Region - Jolbekov, Ibrohim; Farmonqulov, Begzod (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This study is dedicated to the investigation of drying and storage technologies for apple (Malus domestica Borkh.) fruits in the conditions of Sirdarya region. The work analyzes the current state of apple cultivation, the biological and chemical properties of the fruit, and compares the methods of storage in fresh and dried forms. According to the research results, an average of 1.5 tons (15%) of dried product is obtained from 10 tons of fresh apples. The hot and dry climate of the region is favorable for solar drying, which ensures energy efficiency and increases profitability up to 35%. As a result of the study, an effective drying technology suitable for the region and practical recommendations were developed.